Neo-Entrepreneurship as an adaptation model of reindeer herding in Finland - Heikkinen, Hannu (2006)
Reindeer herding is an old an impressively adapted livelihood supporting unique cultural continuity of both Sámi and Finnish populations in northern Finland. Trough centuries both have adapted to the changed to the social, cultural and ecological circumstances. This article focuses on reindeer herders as active conformists who try to adapt personally and communally to changing environments.